Buzzer di Masa Pandemi Covid-19: Studi Analisis Wacana Kritis Kicauan Buzzer di Twitter: STUDY OF CRITICAL DISCOURSE ANALYSYIS OF BUZZER'S TWEET IN TWITTER - Hanif Jati Pambudi; Ario Lukito Adi Nugroho; Liliek Handoko; Firstya Evi Dianastiti (Jurnal Masyarakat dan Budaya, 2021)
The Covid-19 pandemic in Indonesia was widely discussed on social media, such as the Twitter. The widespread use of social media was followed by the emergence of buzzers with their goals and interests as well as  the ideology they promote. One of the buzzers is @ permadiaktivis1, in this case, who has confirmed himself a buzzer. This qualitative research refers to Norman Fairclough's critical discourse analysis by repeating the discussion on the textual dimension, the discourse practice, and the sociocultural dimension. Data obtained from tweets on the Twitter account @ permadiaktivis1 during the Covid-19 pandemic. The Buzzer in this study is positioned as a key opinion leader who is assumed able to polarize information related to the Covid-19 pandemic. the representation of the pandemic imaged as something negative is to negate the government's mismanagement in making policies related to pandemics. The tweets never blame the government for the policies issued, and insinuations and invitations became a pattern for tweets. The vaccination’s policy is packaged that teases those who doubt vaccinations or those who refuse it. The Buzzer phenomenon will impact the polarization of the information about COVID-19. Besides, several tweets from Buzzer show that they play significant role to support government policies.